Management of lower urinary tract obstructive disease using bladder tube cystotomy in a Saanen buck - Khairuddin, Nurul Hayah; Mansor, Rozaihan; Radzi, Rozanaliza; Mohamad Yusof, Loqman (Universiti Putra Malaysia Press, 2016)
This report describes a procedure of bladder tube cystotomy to relieve progressing bladder distension in a goat diagnosed to have obstructive urolithiasis. This one-year old Saanen buck was presented with a complaint of not passing urine and being in discomfort for almost three days. On physical examination, pulsation of the urethra in the perineal region could be felt and swelling and pain along the prepuce and perineum were indicated on deep palpation. Amputation of the urethral orifice and attempt to catheterise the urethra failed to relieve bladder distension; thus, bladder tube cystotomy procedure was performed. Following this procedure, all vital parameters returned to normal and normograde cystourethrogram was performed to radiographically assess the lower urinary tract of the goat. The outcome of this case supports that the bladder tube cystotomy technique provides an effective method to allow immediate relief of a distended bladder, allowing the urethra to heal as the urine outflow is diverted through the catheter and allows normograde cystourethrography to be performed.